1999
DOI: 10.1046/j.1469-8137.1999.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen reserve status affects the dynamics of nitrogen remobilization and mineral nitrogen uptake during recovery of contrasting cultivars of Lolium perenne from defoliation

Abstract: Nitrogen (N) allocated to leaf growth in forage grasses and legumes following severe defoliation is predominately mobilized from the remaining root and leaf sheath tissues, since both N uptake from the soil and N # fixation are severely down-regulated for several days. The hypothesis that a low N reserve status at the time of defoliation limits N remobilization and leaf regrowth was tested with contrasting cultivars of Lolium perenne (cvs Aberelan and Cariad) in flowing solution culture. Plants were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
3
47
2
1
Order By: Relevance
“…Our observation indicated seasonal and successional dynamics in N-form utilization of plant species especially with varying site-specific conditions, such as mineral soil-N concentration or plant interaction (density) which occur during succession (see also Louahlia et al 1999;McKane et al 2002;Jumpponen et al 2002;Kahmen et al 2006). The observation of C. canescens and R. acetosella across three successional stages showed that both species used the same N-sources, but in different amounts.…”
Section: Effects Of Successional Stagesmentioning
confidence: 80%
“…Our observation indicated seasonal and successional dynamics in N-form utilization of plant species especially with varying site-specific conditions, such as mineral soil-N concentration or plant interaction (density) which occur during succession (see also Louahlia et al 1999;McKane et al 2002;Jumpponen et al 2002;Kahmen et al 2006). The observation of C. canescens and R. acetosella across three successional stages showed that both species used the same N-sources, but in different amounts.…”
Section: Effects Of Successional Stagesmentioning
confidence: 80%
“…Like in various other naturally prolineaccumulating plants (Suresh et al, 2008), LP leaves also contain high concentrations of proline (Kemble and MacPherson, 1954). Beside this, LP leaf extract contains significant amounts of various inorganic nutrients and organic compounds like nitrogen, phosphorus, calcium, potassium, magnesium, fiber, carbohydrates, and proteins (Louahlia et al, 1999;Harrington et al, 2006). However, utilization of this natural proline source in mitigating salinity-and/or nickel-induced deleterious effects cannot be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that plant nutrient status at the time of defoliation is an important determinant of subsequent regrowth (Ourry et al 1989, Thornton and Millard 1996, Volenec et al 1996, Louahlia et al 1999.…”
Section: Dynamics Of Plant Regrowth and Plant Morphologymentioning
confidence: 99%
“…Higher contents of nitrates, free amino acids and soluble proteins were frequently observed in plants grown under high N availability (Morvan-Bertrand et al 1999a, Louahlia et al 1999, Gloser 2002. Although the high content of soluble nitrogen compounds is not necessarily connected with rapid plant regeneration, the magnitude and dynamics of mobilization of nitrogen reserves after defoliation usually depends on the plant N status at the time of defoliation (Ourry et al 1989, Louahlia et al 1999. Dependence of defoliated plants on nitrogen and carbon reserves also varies throughout regrowth (De Visser et al 1997, Morvan-Bertrand et al 1999a.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation